2016
DOI: 10.1364/oe.24.020842
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of surface damage precursor evolutions and laser-induced damage threshold improvement mechanism during Ion beam etching of fused silica

Abstract: Surface damage precursor evolution has great influence on laser-induced damage threshold improvement of fused silica surface during Ion beam etching. In this work, a series of ion sputtering experiment are carried out to obtain the evolutions of damage precursors (dot-form microstructures, Polishing-Induced Contamination, Hertz scratches, and roughness). Based on ion sputtering theory, surface damage precursor evolutions are analyzed. The results show that the dot-form microstructures will appear during ion be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…IBE can effectively remove or mitigate surface fracture defects, such as brittle scratches, to improve the laser damage resistance of fused silica. In the previous research, this passivation phenomenon on damage precursors during IBE has been investigated [16,18]. IBE removes the fused silica material and maintains the surface roughness with the help of the ion sputtering effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IBE can effectively remove or mitigate surface fracture defects, such as brittle scratches, to improve the laser damage resistance of fused silica. In the previous research, this passivation phenomenon on damage precursors during IBE has been investigated [16,18]. IBE removes the fused silica material and maintains the surface roughness with the help of the ion sputtering effect.…”
Section: Discussionmentioning
confidence: 99%
“…A peer-reviewed research has shown that IBE can remove polishing residual contamination from the surface of optics to improve LIDT while maintaining surface precision to obtain a supersmooth surface [18][19][20]. As a potential nanometer precision postprocessing technology, IBE can be utilized to mitigate nanoscale damage precursors in the present study [18]. However, many important aspects of IBE for mitigating the nanoscale damage precursors of fused silica remain controversial.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…When the dose of ion beam was very low (<2 × 10 13 cm −2 ), the ion injection would only generate an isolated Frenkel pair (gap–vacancy pair) or a small defect cluster, i.e., vacancy defects [ 27 ]. Meanwhile, as an effective processing method to improve the laser performance [ 28 , 29 ], IBF is usually used to acquire an ultra-smooth surface [ 30 ] or is applied to the precoating cleaning of sample surface [ 31 ]. IBF was performed on the self-developed KDIBF650L-VT machine ( Figure 5 ) and atomic vacancy defects were introduced.…”
Section: Methods Of Defect Regulationmentioning
confidence: 99%
“…Unfortunately, the damage precursors in the subsurface layer such as scratches and embedded impurities are too stubborn to be avoided, even though the surface fabrication level of fused silica optics nearly approach to its limit. Recently, more efforts have been focused on removing the SSD by developing advanced surface modification processes, such as HF-based etching [ 4 , 5 ], ion beam etching (IBE) [ 6 , 7 , 8 ], magnetorheological polishing (MRF) [ 9 ] and reactive ion etching (RIE) [ 10 , 11 ]. Comparing the different attempts at surface modification for fused silica, the last-mentioned RIE technique exhibits some distinct advantages.…”
Section: Introductionmentioning
confidence: 99%